Tipificar en el Código Orgánico Integral Penal la Conducta Antijurídica de la Zoofilia - Macas Quezada, Martha Guadalupe (2018)
Zoophilia is the realization of the sexual act between a human being and an animal, this act is considered unnatural. The zoophilia has been practiced since ancient times and in rural areas more frequently. Many psychological studies about this paraphilia, treat it as a sexual disorder of the human being and among the causes for the practice of zoophilia are the isolation, little capacity to carry out social relations, absence of couple among others. Medical studies have confirmed that the practice of Zoophilia can be an indicative or consequence of penile cancer in men since the contact of animal fluids called zoonosis can result not only in the disease but also in other bacterial types. The social and legal issues not only lies in the above mentioned if not when the zoophile sexually accesses the animal because it is attacking their rights because not being a normal sexual act, the animal is being mistreated, injured and many times this can cause his death. In view of this, our Comprehensive Criminal Organic Code does not typify Zoophilia as an offense or contravention, so that the animals that are victims of such an act remain totally unprotected. In my opinion of value this situation is unsustainable since as a country we have advanced in legal regulations since the constitutional reform of 2008, however there are legal gaps that are still allowing legal unprotection in the exercise and respect of the rights of nature as they are animal rights is why a number of animal rights activists and society in general fight every day to avoid animal abuse but in cases of zoophilia nothing can do because the criminal law of our country is retrograde to protect the animals of this type of conducts that occur 6 frequently in our society and that for the victims the animals little importance is given to them. In view of the social and legal issues, I have considered it convenient to make a theoretical, doctrinal and legal study as a basis for the criminalization of Zoophilia as an offense in the Organic Comprehensive Penal Code, so I bring to light this work carried out from the conceptual contributions, doctrinal and legal; taking into account the great contribution of field work obtained from the application of surveys and interviews, which centrally involves the problem. The legal research was developed with the analysis of the Ecuadorian legislation in hierarchical form from the Constitution of the Republic of Ecuador, Comprehensive Criminal Code, and criminal law of different countries what has been able to successfully carry out the investigation, and not to mention the different bibliographical sources that explain concepts, definitions, historical antecedents, theoretical and relevant aspects about zoophilia, it is so that throughout the process and research development an efficient work is demonstrated in the analysis and foundation of the problem, both in relation to the literature review and even more in the analysis of the results of the field research. They are also the body of this research work, an accomplished detail of the different materials, methods, procedures and techniques used to obtain valid and sustainable data. In conclusion after all an investigative work I can say that a legal reform of the Integral Organic Penal Code is necessary in order to typify Zoophilia as a crime.